Identificação e estimativa da idade larval de espécies necrófagas de "Calliphoridae" (Insecta, Diptera) por meio de morfometria geométrica : Identification and estimation of larval age of necrophagous species of "Calliphoridae" (insecta, Diptera) using geometric morphometrics - Maia, Bárbara Maria Cerqueira, 1996- (2023)
Orientador: Patrícia Jacqueline Thyssen